The UCLA Anderson Business and Information Technologies (BIT) Project : A Global Study of Technology and Business Practice (2016) - Mangal, Vandana , editor; Karmarkar, Uday , editor; Mandelli, Andreina , editor; Rocca, Antonella La , editor; UCLA Anderson Business and Information Technologies (BIT) Project (New Jersey : World Scientific, 2016)
Includes bibliographical and references